2014
DOI: 10.1021/cs400908h
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Characteristics of Ceria under Ethanol Steam Reforming Conditions: Effect of the Particle Size

Abstract: Reducibility of ceria under steam reforming conditions and the effect of particle size on its reducibility was examined using two ceria samples with distinctly different mean particle sizes (3.5 nm versus 120 nm), but with similar polyhedral morphologies. The degree of reduction from Ce 4+ to Ce 3+ was characterized by temperature programmed reduction (TPR) and in situ X-ray absorption near edge structure spectroscopy (XANES) where the nanopolyhedra were observed to reduce much more readily compared to the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 52 publications
3
63
0
1
Order By: Relevance
“…A VG Scienta R4000 HiPP analyzer was used for XPS analysis. 24 The O 1s region was probed with photon energy of 650 eV, and the C 1s, Ni 3p, and Ce 4d 6 regions with photon energy of 490 eV and a resolution of ~0.2 eV. The Ce 4d photoemission lines were used for binding energy calibration based on the 122.8 eV satellite features.…”
Section: Methodsmentioning
confidence: 99%
“…A VG Scienta R4000 HiPP analyzer was used for XPS analysis. 24 The O 1s region was probed with photon energy of 650 eV, and the C 1s, Ni 3p, and Ce 4d 6 regions with photon energy of 490 eV and a resolution of ~0.2 eV. The Ce 4d photoemission lines were used for binding energy calibration based on the 122.8 eV satellite features.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the adsorption of ethanol (as ethoxy species) onto metallic particles [30,57] is considered as the initial step of EtOH transformation (1) [31,58]. Ethanol, similarly to other alcohols, also dissociatively adsorbs on ceria [7,[59][60][61]; however, studies of Soykal et al [4,62] and Song et al [16] have shown that bare ceria exhibits rather poor activity in CAC bonds cleavage in temperature range of 400-450°C. Studies of da Silva et al suggest that an EtOH conversion of $50% can be achieved at 500°C with EtOH/H 2 O = 1/3 mol/mol [61,63].…”
Section: Effect Of the Surface State On The Esr Reaction Products Yieldmentioning
confidence: 99%
“…Recently, it was demonstrated that the catalytic performance of CeO 2 depends on the particle size, due to the difference of the reducibility and therefore the number of acidic sites. 37 Depending on the degree of ceria reduction, unique reactivity profiles can also be observed on ceria-supported Rh catalysts. For example, while CO adsorbs non-dissociatively on Rh nanoparticles on fully oxidized ceria films, it dissociates on partially reduced films.…”
Section: +mentioning
confidence: 99%